Analisis Tingkat Stres Mahasiswa dengan Kuliah Daring di Masa Pandemi Covid-19 - Erviana Erviana; Jusman Jusman; Indrawati Indrawati (KOLONI, 2022)
The Corona virus pandemic or Covid-19, is the main priority cause of current health problems for all individuals, groups, nations and countries. The impact of corona or Covid-19 has greatly affected all sectors, especially the education sector in universities. The impact of Covid has forced the government to issue policies regarding the implementation of lectures which are usually conducted face-to-face and become brave (online). The purpose of this research is to determine the description of students' stress levels during brave lectures. Method: This research uses quantitative descriptive methods. The population of this study were Nursing study program students class of 2019, Faculty of Health Sciences, University of West Sulawesi (UNSULBAR). Results: In this study, it was found that the majority of students experienced mild stress (42.3%), normal stress (25.4%), moderate stress (23.9%), severe stress (7%), and very severe stress (1 , 4%).Conclusion, this research shows that the majority of Class of 2019 students of the Nursing Study Program, Faculty of Health Sciences, University of West Sulawesi (UNSULBAR) experienced mild stress in the dare learning system in the era of the COVID-19 pandemic.